Ariki and the giant shark - Davies, Nicola 1958- (Walker Books, 2018)
Washed up on Turtle Island as a toddler, Ariki has always felt different from the other children. But there's somewhere she belongs heart and soul: the sea, where she plays with dolphins, sharks, whales and turtles. One day Ariki catches sight of a strange creature in the water, bigger than any she's seen before - soon after, an enormous shark tooth is found on the sand. When a group of giant sharks start circling the shore, the island's fishermen are too afraid to go out to sea. Without fish the people will starve ... Can Ariki save the day?
Keywords: Ariki / (Fictitious character) / Juvenile fiction; Girls / Juvenile fiction; Sea stories; Sharks / Juvenile fiction; Children's stories; Sharks; Girls